2019
DOI: 10.1155/2019/7676341
|View full text |Cite
|
Sign up to set email alerts
|

Characterising SRD5A2 Gene Variants in 37 Indonesian Patients with 5-Alpha-Reductase Type 2 Deficiency

Abstract: The 5-alpha-reductase type 2 deficiency (5ARD2) is an autosomal recessive condition associated with impairment in the conversion of testosterone to dihydrotestosterone. This condition leads to undervirilisation in 46,XY individuals. To date, there have been more than 100 variations identified in the gene responsible for 5ARD2 development (steroid 5-alpha-reductase 2, SRD5A2). However, few studies have examined the molecular characterisation of Indonesian 5ARD2 cases. In the current study, we analysed 37 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…They discovered that among 37 subjects, there were twelve variants of the SRD5A2 identified and 6 of which were novel. They also agreed with Avedaño et al in which the mutations themselves produce deficiency at different levels of severity [ 6 ]. More severe diseases produce subjects with lower EMS.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…They discovered that among 37 subjects, there were twelve variants of the SRD5A2 identified and 6 of which were novel. They also agreed with Avedaño et al in which the mutations themselves produce deficiency at different levels of severity [ 6 ]. More severe diseases produce subjects with lower EMS.…”
Section: Discussionsupporting
confidence: 85%
“…Type 2 5α-reductase deficiency is an autosomal recessive condition involving the SRD5A2 gene on chromosome 2p23 [ 6 , 7 ]. The enzyme 5 α-reductase is required for the conversion of testosterone (T) to dihydrotestosterone (DHT) through a double-bond reduction with NADPH as a cofactor [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that, due to lack of precise cut-off in T/DHT ratio in hormonal findings, correct diagnosis of patients with DSD, as presented in this study, is unreliable, which suggest the requirement of sequence analysis of AR and SRD5A2 genes to precisely reach the clinical diagnosis (Ahmadifard et al, 2019;Marzuki, Idris, Kartapradja, Harahap, & Batubara, 2019). In the studies similar to this study, it was suggested to get the benefit of comprehensive NGS-targeted panel with multiple DSD-related genes or WES, rather than NGS one targeted gene analysis (Dong et al, 2016;Eggers et al, 2016;Hughes et al, 2019;Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 70%